The Planning and Creation of an E-Learning and Recreational Platform for Seniors - Ricardo de Freitas; O'Neill, Henrique (CAFVIR 2013 - IV Congresso Internacional sobre Qualidade e Acessibilidade da Formação Virtual, 2013)
Using E-Learning platforms is a great way for older people to learn and also to share the knowledge and experience gained during the course of their lives. However, the level of complexity of these platforms may arise as an obstacle for seniors. The main objective of this article is to plan and create the prototype of an E-Learning and recreational platform specifically designed for seniors. After planning the prototype, a requirements study was performed in order to gather feedback from our target group before commencing with the development phase. Once the development phase was complete, a usability study was carried out to test how seniors interacted with the prototype. These studies mainly revealed the various types of difficulties experienced by seniors when using a traditional E-Learning website. These difficulties were accounted for when creating the E-Learning platform for seniors.